Skills and Inclusive Growth in Sweden - Pareliussen, Jon (OECD Publishing, 2015)
A highly skilled workforce is crucial to sustain competitiveness and contain the rise in income inequality. Recent surveys of adult skills and educational performance suggest that younger cohorts are doing less well than their predecessors. Many immigrants struggle both in school and in the labour market partly because of low skills and language difficulties. Educational outcomes could be improved through raising the attractiveness of the teacher profession, improving teacher education and increasing support for struggling students. A more flexible labour market would facilitate access to jobs for youth with low qualifications and immigrants. This Working Paper relates to the 2015 OECD Economic Survey of Sweden www.oecd.org/eco/surveys/economic-survey-sweden.htm
Keywords: Economics; Sweden